Open-label phase I clinical trial of Ad5-EBOV in Africans in China - Lihua Wu; Zhe Zhang; Hainv Gao; Yuhua Li; Lihua Hou; Hangping Yao; Shipo Wu; Jian Liu; Ling Wang; You Zhai; Huilin Ou; Meihua Lin; et al. (Taylor & Francis Group, 2017)
Background: To determine the safety and immunogenicity of a novel recombinant adenovirus type 5 vector based Ebola virus disease vaccine (Ad5-EBOV) in Africans in China. Methods: A phase 1, dose-escalation, open-label trial was conducted. 61 healthy Africans were sequentially enrolled, with 31 participants receiving one shot intramuscular injection and 30 participants receiving a double-shot regimen. Primary and secondary end points related to safety and immunogenicity were assessed within 28 d after vaccination. This study was registered with ClinicalTrials.gov (NCT02401373). Results: Ad5-EBOV is well tolerated and no adverse reaction of grade 3 or above was observed. 53 (86.89%) participants reported at least one adverse reaction within 28 d of vaccination. The most common reaction was fever and the mild pain at injection site, and there were no significant difference between these 2 groups. Ebola glycoprotein-specific antibodies appeared in all 61 participants and antibodies titers peaked after 28 d of vaccination. The geometric mean titres (GMTs) were similar between these 2 groups (1919.01 vs 1684.70 P = 0.5562). The glycoprotein-specific T-cell responses rapidly peaked after 14 d of vaccination and then decreased, however, the percentage of subjects with responses were much higher in the high-dose group (60.00% vs 9.68%, P = 0.0014). Pre-existing Ad5 neutralizing antibodies could significantly dampen the specific humoral immune response and cellular response to the vaccine. Conclusion: The application of Ad5-EBOV demonstrated safe in Africans in China and a specific GP antibody and T-cell response could occur 14 d after the first immunization. This acceptable safety profile provides a reliable basis to proceed with trials in Africa.